Economic and Demographic Effects of External Migration in Poland and Slovakia - Some Aspects - Skibiński, Andrzej; Rączaszek, Andrzej (European Journal of Sustainable Development, 2017)
The paper presents the external migration flows and their impacts on economic and social life in analyzed countries. The travel inside the EU is totally free after Poland and Slovakia joined the EU, and they fructified this opportunity. There are important economic consequences of these movements, because external migration is an ever-growing phenomenon that has important development implications for both sending and receiving countries. For a sending country migration and the resulting remittances lead to increased incomes and educational outcomes, and promote economic development. On the other hand, migration processes influence on changes in the age structure. This process is very important from the labour market point of view. Hence, the aim of this publication is to identify the post-accession effects of foreign migration, especially the consequences for the labour market in Poland and Slovakia. Applied quantitative and qualitative analyses were conducted based on survey results and data from Eurostat statistical databases. The survey was conducted since March – till April 2017 on a sample of N = 254 respondents, using the diagnostic survey method. The temporal scope of the analyses was largely determined by data accessibility. Keywords: labour market, migration processes, aging population